Supporting data set for: Simulations of the Electrochemical Oxidation of Shape-Selected Nanoparticle Catalysts ... - Kirchhoff, Björn; Jung, Christoph; Jónsson, Hannes; Fantauzzi, Donato; Jacob, Timo (Zenodo, 2022)
This dataset contains input and output files for simulations of the oxidation of a set of shape-selected, 3 nm platinum nanoparticles associated with the manuscript found at https://arxiv.org/abs/2201.07605. The simulations are performed using a grand-canonical Monte-Carlo algorithm[1,2] in combination with the ReaxFF reactive force field method as implemented in the Amsterdam Density Functional (ADF) software package version 2017.106 by Software for Chemistry and Materials (SCM). The Pt/O ReaxFF force field parameterized by Fantauzzi et al. was used for the simulations.[3] Simulations were performed at oxygen chemical potential conditions corresponding to 200-1000 K at ultra-high vacuum (UHV, p O2 = 10 -10 mbar) and 400-1200 K at near-ambient pressure (NAP, p O2 = 1 mbar) conditions. The following nanoparticle shapes were used as input structures for the simulations: (111)-indexed octahedron, (100)-indexed cube, (110)-indexed dodecahedron, (111)- and (100)-indexed cuboctahedron, mixed-indexed sphere, and ... : This work was supported by Deutsche Forschungsgemeinschaft (DFG) through the collaborative research center SFB-1316 as well as the priority program SPP-2080. The state of Baden-Württemberg is acknowledged through bwHCP and DFT through grant no INST 37/935-1 FUGG. The Volkswagen Group Wolfsburg is acknowledged for partial funding, as well as the Icelandic Research Fund. BK acknowledges the University of Iceland Research Fund for funding through a PhD fellowship. ...